Comparison of Value at Risk (VaR) in Risk Analysis: Historical, Variance Covariance and Monte Carlo Methods - Fauziyah, Meirinda; Dani, Andrea Tri Rian; Koirudin, Hadi; Budi, Ennesya Estya; Avrilia, Khairunnisa; Watika, Noor Hikmah (Darul Yasin Al Sys, 2024)
Value at Risk (VaR) is a method used to measure financial risk in a company. VaR calculations are often used to calculate the level of loss from shares in a company, such as bank shares. The aim of this research is to determine the level of losses in Bank Central Asia shares using the historical method, the Variance-covariance method, and the Monte Carlo method. the results showed that with an initial investment of 50 and using the Historical method at a significant level of 95%, the VaR value was obtained at 16.42 or IDR. 267.301 and at the 90% significant level, the VaR value was obtained at 12.41 or IDR. 202.022. Based on the Variance-covariance method with an initial investment of 50 at the 95% significant level, the VaR value is obtained at 16.42 or IDR. 267,301 and at the 90% significant level, the VaR value is obtained at 12.79 or IDR. 208.208. Meanwhile, based on the Monte Carlo method with an initial investment of 50, at a significant level of 95%, the VaR value is obtained at 16.46 or IDR. 267,952 and at the 90% significance level, the VaR value is obtained at 12.84 or IDR. 209.022. Based on the three methods used, it was concluded that the Monte Carlo method gave greater results compared to the other two methods.